Analysing the dynamics of land use in the context of current conservation policies and land tenure in the Cerrado – MATOPIBA region (Brazil). (October 2021) - Polizel, Silvia Palotti; Vieira, Rita Marcia da Silva Pinto; Pompeu, João; Ferreira, Yara da Cruz; Sousa-Neto, Eráclito Rodrigues de; Barbosa, Alexandre Augusto; Ometto, Jean Pierre Henry Balbaud
Abstract: The side effect of the expansion of agricultural activities in the Brazilian Cerrado resulted in a loss of its native vegetation, biodiversity decline, and increasing greenhouse gas emissions. Recent expansion has mainly occurred in the northern Cerrado, a region known as MATOPIBA, which is the latest agricultural frontier in Brazil and is largely cultivated for agricultural commodities. In this paper, we investigate the spatiotemporal behaviour of Cerrado vegetation and agricultural areas in the Cerrado – MATOPIBA (CM) region between 1990 and 2017. Moreover, we analyse the planted area expansion of soybean and other important crops for the region and their productivity, and examine how pasturelands have changed over time. We also present a map of private rural lands and analyse whether they comply with the national Forest Code (FC) regarding in-farm areas of natural vegetation that ought to be preserved by law. Finally, we estimate how much of the current deforestation rates could be avoided in the CM region if the Soy Moratorium (SoyM) or the FC are implemented. Results show a loss of almost 8.4 Mha of the Cerrado vegetation in the study area and an expansion of 4.3 Mha of agricultural lands between 1990 and 2017. Our analysis indicates that soybean planted areas expanded by 326% between 2000 and 2017 and that soybean average productivity increased from 2483 kg/ha in 2000 to 2906 kg/ha in 2017. In addition to soybean, other crops also contributed to the agribusiness economy in the CM region, with corn being the crop with the greatest expansion of planted areas over the same period (643, 443 ha), and cotton the cultivation with the highest increase in productivity (from 2300 kg/ha to 3822 kg/ha) in these 17 analysed years. Pasturelands expanded from 6.4 Mha in 2000 to 9.8 Mha in 2017. In 2018, private rural properties consisted of only 7188 large properties and occupied 19.5 Mha, whereas small and medium properties accounted for 136, 586 farms and covered a total of only 17.5 Mha. With respect to the national FC, the deficit of preservation areas in the CM region, in relation to the agricultural area of each municipality, totalled almost 1.4 Mha in 2017, with large properties responsible for 57% of this deficit. Looking at the policies and mechanisms to protect the native vegetation of the CM region, we have that 17, 219, 250 ha can still be legally deforested on the rural properties in this region; and, if the SoyM was expanded to the Cerrado – MATOPIBA region, almost 900, 000 ha covered by native vegetation on the categories of farms selected would have been prevented to be converted to soybeans since 2010. The findings from this paper provide a comprehensive understanding of the land use and land cover changes and of the Cerrado deforestation patterns in the CM region for the last decades, and gather information on conservation policies in place to suggest improvements. Several datasets were combined, mainly focus on quantitative analysis, to investigate the geospatial dynamics of natural and agribusiness areas in the study region, and suggest the need to reinforce the preservation of Cerrado native vegetation areas, particularly those that are liable to be legally deforested. Highlights: There are 21.5 Mha of native vegetation covering private rural properties. 17.2 Mha of these vegetation areas can be legally deforested. Legal mechanisms are not strong enough in the region, as only 4.3 Mha of native vegetation is protected. Agricultural areas expanded by 645% in the CM region between 1990 and 2017. In 2020, the CM region was responsible for 64% of the Cerrado's deforestation.